2021
DOI: 10.1177/20551029211018378
|View full text |Cite
|
Sign up to set email alerts
|

Does culture moderate the relationship between body dissatisfaction and quality of life? A comparative study of Australian and Malaysian emerging adults

Abstract: Investigating moderating effects of culture between body dissatisfaction (BD) and quality of life (QoL) is paramount, as BD affects psychosocial functioning. Participants include 866 females (18–25) years old from Australia ( n = 464) M (20.88) SD (3.38) and Malaysia ( n = 402) M (20.63) SD (2.05). Higher levels of BD predicted lower levels of QoL across all four domains. BD had the strongest effect on psychological QoL for both cultures. Culture moderated the relationship between BD and: (i) physical QoL and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Patterns of body dissatisfaction may be more impacted by sociocultural zeitgeists than body size estimation. Media representation of an ideal body type (Bennett et al, 2020; Marques et al, 2022), cultural-based differential influences (Santhira Shagar et al, 2021), and peer influences or family dynamics (Helfert & Warschburger, 2011; Michael et al, 2014) have been documented to contribute to the development of body dissatisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Patterns of body dissatisfaction may be more impacted by sociocultural zeitgeists than body size estimation. Media representation of an ideal body type (Bennett et al, 2020; Marques et al, 2022), cultural-based differential influences (Santhira Shagar et al, 2021), and peer influences or family dynamics (Helfert & Warschburger, 2011; Michael et al, 2014) have been documented to contribute to the development of body dissatisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…As documented in other cultural contexts, in Asian countries body image concerns have been associated with eating disorder symptoms (Yamamiya et al, 2008 ; Chisuwa and O’Dea, 2010 ; Kaewpradub et al, 2017 ), depression (Prusaczyk and Choma, 2018 ), and poorer quality of life (Santhira Shagar et al, 2021 ). In very recent years, prevention efforts have been extended to affluent and developing areas of Asia (Craddock et al, 2021 ; Danthinne et al, 2022 ; Garbett et al, 2022 ); however, more work is needed.…”
Section: Empirical Evidence Across Countriesmentioning
confidence: 93%
“…Increased body dissatisfaction is associated with decreased psychological, social, and physiological quality of life in women (Mond et al, 2013) and adolescent boys and girls (Griffiths et al, 2017). Research has also demonstrated that increased body dissatisfaction in women is associated with each domain of quality of life (Santhira Shagar et al, 2021). While a similar pattern has emerged in men in some specific domains, such as psychological and physiological quality of life (Griffiths et al, 2016(Griffiths et al, , 2018(Griffiths et al, , 2019, no research has comprehensively examined how body dissatisfaction is associated with quality of life across each domain in men.…”
Section: Body Dissatisfaction and Quality Of Lifementioning
confidence: 99%
“…Environmental quality of life may equally be impaired, as body dissatisfaction may create a hostile and confrontational environment, marked by the belief that one's body is being observed, objectified, and judged (Brewster et al, 2017;Santhira Shagar et al, 2021). Further, according to sociocultural theories of body dissatisfaction, appearance-related messages (e.g., unrealistically muscular ideals) from society contribute to poor body image (Tylka, 2011).…”
Section: Body Dissatisfaction and Quality Of Lifementioning
confidence: 99%
See 1 more Smart Citation